From symptoms to surgery: clinicopathological correlation in women undergoing hysterectomy for abnormal uterine bleeding - Banmeru, Ashwini P.; M., Narayanaswamy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) is one of the most frequently encountered conditions in women which is defined as any variation from the normal menstrual cycle which includes changes in regularity, frequency of menses, duration of flow, or amount of blood loss. The PALM-COEIN system classifies different causes of AUB and is composed of nine basic categories arranged according to the acronym PALM-COEIN as polyp, adenomyosis, leiomyoma, malignancy and hyperplasia, coagulopathy, ovulatory disorders, endometrial, iatrogenic, and not yet classified. Definitive treatment of AUB is hysterectomy even though less invasive options are also available. This study explored clinicopathological correlation in women undergoing hysterectomy, analysing the diagnostic criteria, clinical presentations, histopathological findings with an aim of establishing better therapeutic strategies and improving patient management and in further research for comparative and epidemiological studies in diagnostic approaches for AUB in various population. Methods: This was prospective observational type of study which included 126 women with abnormal uterine bleeding (AUB) planned for hysterectomy at SNR district hospital, Kolar during the study period. Detailed history, required investigations were done. Study material was from hysterectomy specimens of the patients who underwent total abdominal hysterectomy (TAH) or vaginal hysterectomy for abnormal uterine bleeding (AUB). Data of clinically diagnosed cases, USG report and histopathological reports (of endometrial tissue) was collected and compared to find the correlation. Results: A total of 126 women underwent hysterectomy in the study period. Heavy menstrual bleeding (HMB) was commonest presentation (60%) followed by dysmenorrhoea (55%) and irregular menstrual bleeding (52%). AUB-L was commonest cause for AUB clinically (51.58%), sonologically (51.58%) and histopathologically (49.20%), followed by adenomyosis on USG (17.46%) and histologically (16.66%) and clinically followed by the cases without any organic pathology (AUB-O) (42.85%). Conclusions: The present study confirms a good correlation between clinical findings and histopathology especially in benign conditions.